A Time-Series Analysis of the "Bills-Only" Theory of Interest Rates - Fand, David I. (The Review of Economics and Statistics, 1966)
I N 1953 the Federal Open Market Committee concluded that it was desirable to confine its open market transactions to short-term securities, preferably Treasury bills. This policy was announced to the public in a speech by Chairman Martin, Transition to Free Markets, and has subsequently been called the bills-only policy.' Federal Reserve operations were to be limited to those necessary for supplying or withdrawing reserve funds and the authorities would not ordinarily intervene to prevent fluctuations in prices or yields of government securities. With very few exceptions, the Federal Reserve followed these principles, and open market transactions in Treasury certificates, notes and bonds were virtually eliminated. Except for 1955, and in 1958 when the market approached disorderly conditions, the Federal Reserve held its operations in certificates, notes, and bonds to something like one per cent of its total open market transactions. The policy was discarded in early 1961 when we were confronted with a balance-of-payments deficit at a time when the economy was operating at close to recession levels. In this paper, we present a statistical investigation of the movements in interest rates since 1953 to determine whether they conform to the suppositions of the bills-only theory. The substantive propositions of this theory concerning interest rate behavior are summarized in section I. In section II, we suggest several tests of this theory and summarize the statistical evidence. The conclusions are presented in section III.